2013
DOI: 10.3109/2000656x.2013.787936
|View full text |Cite
|
Sign up to set email alerts
|

Slow progression predicts poor prognoses in patients with spontaneous posterior interosseous nerve palsy

Abstract: There are still no factors that predict the prognoses of patients with spontaneous posterior interosseous nerve palsies who are in an early phase of the illness. This paper reviewed 39 patients with this type of palsy. Seventeen patients who requested surgery for possible earlier recovery underwent interfascicular neurolysis because no signs of recovery were seen more than 3 months after onset. A Medical Research Council muscle power grade over 4 at their final visit was considered a good result, while a power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Both those who believe the condition is due to neuralgic amyotrophy and those who believe it is caused by fascicular constriction favour conservative treatment in children. However, in adults, slow progression of the palsy for more than a month is one of the poor prognostic factors associated with conservative treatment (Ochi et al, 2013), which also was the case in our two paediatric cases. We therefore conclude that surgical treatment should be considered, not only in adult-onset spontaneous PIN palsy, but also in children if there is no spontaneous recovery or even slow worsening of the palsy during conservative treatment.…”
supporting
confidence: 74%
“…Both those who believe the condition is due to neuralgic amyotrophy and those who believe it is caused by fascicular constriction favour conservative treatment in children. However, in adults, slow progression of the palsy for more than a month is one of the poor prognostic factors associated with conservative treatment (Ochi et al, 2013), which also was the case in our two paediatric cases. We therefore conclude that surgical treatment should be considered, not only in adult-onset spontaneous PIN palsy, but also in children if there is no spontaneous recovery or even slow worsening of the palsy during conservative treatment.…”
supporting
confidence: 74%
“…Her palsy kept on proceeding for more than 3 months (slow progression) 2) with no apparent cause. Although she visited several hospitals, her palsy remained undiagnosed and untreated for 17 years.…”
Section: Case Reportmentioning
confidence: 99%
“…Recent studies have demonstrated that age at onset, preoperative delay, complication of ulnar nerve or C8 palsy, surgical finding of fascicular constriction, and progression of palsy significantly correlate with its prognosis. 1,2) However, the therapeutic approach for incomplete spontaneous PIN palsy in which the onset occured more than a year before surgical treatment still remains controversial. Here, we present a case of spontaneous PIN palsy undergoing interfascicular neurolysis with a surgical delay of 17 years.…”
Section: Introductionmentioning
confidence: 99%